Recent Developments in Palladium-Catalysed Non-Directed C–H Bond Activation in Arenes - Kancherla, Sindhu; Jørgensen, Kåre B.; Fernández-Ibáñez, M. Ángeles (Synthesis, 2019)
Over the past decades, organic chemists have focussed on developing new approaches to directed C–H functionalisations, where the site selectivity is steered by the presence of a directing group (DG). Nonetheless, in recent years, more and more non-directed strategies are being developed to circumvent the requisite directing group, making C–H functionalisations more generic. This short review focuses on the latest developments in palladium-catalysed non-directed C–H functionalisations of aromatic compounds.1 Introduction2 C–C Bond Formation2.1 C–H Arylation2.2 C–H Alkylation2.3 C–H Alkenylation2.4 C–H Carbonylation3 C–Heteroatom Bond Formation3.1 C–O Bond Formation3.2 C–N Bond Formation3.3 C–S Bond Formation4 Conclusion
Keywords: C–H bond activation; palladium; non-directed; arenes; catalysis